Spatial Database Mapping Of Paddy Fields For Agricultural Extension Workers In Banjarmasin City, South Kalimantan - Ayuningtyas, Efrinda Ari; Ilmi, Bahrul; Bisa, Gerarda Anastasya; Nabila, Anandia (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
A Geographic Information System (GIS) is a set of systems that can be used for agricultural purposes, presenting a geospatial database of agricultural land. This database can be created using field survey data, collected using the Avenza Maps application installed on a smartphone. The data can then be presented as maps using ArcGIS software. Agricultural extension workers, Indonesia's primary agricultural development agents, must be equipped with the requisite skills to operate geospatial surveying and mapping tools. This is essential for the continuous updating of the agricultural database. The methodology employed in this service is a survey method utilizing a participatory geospatial approach, wherein farmers own the paddy fields and agricultural extension workers act as mappers. The data obtained from geotagging survey results is a crucial input for producing a map of paddy fields in each Banjarmasin City, South Kalimantan urban village. The value of this mapping lies in its potential to enhance the abilities and skills of agricultural extension workers in Food Security, Agriculture, and Fisheries Office of Banjarmasin City and initiate the procurement of a geospatial database of agricultural extension workers and a geospatial database of agricultural land at the local government level. Furthermore, the information and maps of rice fields in Banjarmasin City can be made available to the public and updated as needed.